Inheritance patterns of pomological traits in walnut hybridization breeding: influence of parental varieties on nut traits - Akide Özcan; Huri Taşcı; Şakir Burak Bükücü; İlker Büşah Ayaz; Mehmet Sütyemez (BMC Plant Biology)
Abstract Background Walnut (Juglans regia L.) breeding programs aim to develop new genotypes that exhibit superior agronomic traits, including high yield, improved nut quality, and favorable phenological traits. One of the primary methods used in these programs is hybridization, which involves controlled crosses between selected parent varieties. In reciprocal cross, understanding the genetic contributions of both maternal and paternal parents is crucial, as these contributions significantly influence the phenotypic traits of the resulting progeny. This knowledge allows breeders to predict and select genotypes that best meet the desired breeding objectives, ultimately enhancing agricultural productivity and sustainability. Results This study analyzed the pomological traits of F1 plants derived from four different hybrid combinations: Pedro × Maraş 18, Pedro × Sütyemez 1, Maraş 18 × Pedro, and Sütyemez 1 × Pedro. The assessment focused on key nut traits, including nut length, nut diameter, nut weight, kernel weight, and kernel percentage. Statistical analyses revealed significant variations in these traits among the hybrid combinations, with these differences determined at the p < 0.05 significance level. Kernel weight exhibited the highest coefficient of variation (CV = 33.63%), indicating substantial variability in this trait among the hybrids. Nut diameter had the lowest variability (CV = 12.82%), suggesting greater consistency across the hybrid combinations. Other traits, such as nut weight, nut length, and kernel percentage, showed intermediate levels of variability, with CVs of 27.33%, 13.45%, and 18.59%, respectively. The study found that maternal parents played a more partially dominant role in determining nut traits in most hybrid combinations. However, when Sütyemez 1 and Maraş 18 were used as maternal parents, their influence on the inheritance of some nut traits was relatively greater than the other parent variety (Pedro). Conclusion The findings emphasize the crucial role of parent selection in walnut hybridization breeding programs, with parental effects being relatively prominent in influencing pomological traits, underscoring the need for careful selection of maternal parents to achieve the desired outcomes. Among the varieties studied, Pedro, Maraş 18, and Sütyemez 1 were identified as promising parent genotypes for improving key nut traits. The variability observed in traits such as kernel and nut weights suggests potential for further selection and genetic improvement. This variation highlights the genetic diversity present in the studied hybrids, which can be effectively utilized in breeding efforts. These results not only contribute to the improvement of walnut varieties but also have broader implications for global walnut production, providing valuable guidance for breeding programs aiming to improve nut quality in walnut hybridization programs.